Integration of Artificial Intelligence in Inclusive Education: Comparative Analysis of Uzbekistan, CIS Countries, and International Practices - Dustnazar Omonovich Khimmataliev; Nilufar Parda Qizi Omonova (PT. Pusmedia Group Indonesia, 2025)
This comprehensive systematic review utilized the PRISMA methodology to examine 45 peer-reviewed scholarly articles meeting specific criteria: (1) published during 2021-2024, (2) concentrated on AI implementation within inclusive educational contexts, (3) comprised empirical investigations or review analyses, and (4) accessible in English language. The analysis categorizes AI implementations into three primary domains: (1) supportive technologies for accessibility (representing 40% of examined studies), (2) individualized instructional systems (accounting for 35%), and (3) administrative automation tools (comprising 25%). Artificial Intelligence represents a transformative instrument within inclusive educational frameworks, facilitating customized learning experiences and enhancing educational access for learners with diverse abilities. This investigation delivers an in-depth and methodical examination of AI's influence on inclusive pedagogy, analyzing scholarly works published from 2021 through 2024 across major academic databases including Scopus, Web of Science, and ScienceDirect. The findings demonstrate that AI strengthens accessibility via adaptive resources, including visual content interpretation for students with sight impairments and audio-textual materials for learners with auditory challenges. Furthermore, it diminishes educators' clerical burden, enabling greater dedication to instructional mentorship. Concurrently, multiple obstacles persist, encompassing limited AI competency training, infrastructural deficiencies, disparate technological access, and privacy-related ethical concerns. Ultimately, AI presents considerable opportunities for advancing inclusive education and broadening access. Nevertheless, successful implementation necessitates addressing these substantial challenges. The research presents an integrated scholarly perspective on the merits, obstacles, and future possibilities of incorporating AI within inclusive educational settings.